Broadband and fabrication tolerant polarization splitter–rotator on thin-film lithium niobate - Chijun Li; Geng Chen; Yuankang Huang; Siyu Lu; Zong Wang; Yiqi Dai; Cheng Zeng; Jinsong Xia (APL Photonics)
On-chip polarization splitter–rotators (PSRs) are crucial components for coherent optical communication and polarization-division multiplexing systems. Here, we propose and experimentally demonstrate a polarization splitter–rotator based on the principles of adiabatic mode evolution and the stimulated Raman adiabatic passage on the thin-film lithium niobate (TFLN) platform. The experimental results indicate that the fabricated device exhibits an insertion loss of less than 0.5 dB and extinction ratios exceeding 20 dB over a 130-nm band, with the potential to extend up to 250 nm as predicted by simulations. Large fabrication tolerance is also demonstrated with extinction ratios of more than 20 dB in the wavelength range of 1500–1630 nm. The demonstrated PSR could become an indispensable component in the future TFLN photonic integrated circuits.